Case report: Therapeutic use of bortezomib in a patient with Schnitzler syndrome - Bai, Hua; Zhou, Dongming; Liu, Jinwen; He, Jie; Min, Zhou; Fan, Wenyong; Chen, Bing; Xu, Yong (Frontiers in Immunology, 2025)
Schnitzler syndrome (SchS) is a rare acquired systemic autoinflammatory disorder, characterized by chronic urticarial rash and immunoglobulin M (IgM) monoclonal gammopathy. Anti-interleukin-1 (IL-1) therapies have been shown to be more effective in managing the clinical symptoms of SchS compared to anti-IL-6 therapies. In this case report, we present a male patient with urticarial rash, fever, and arthralgia. Laboratory tests identified the presence of IgMκ monoclonal protein, and the absence of IL-1β in serum. Whole exome sequencing (WES) did not reveal any pathological variants associated with monogenic autoinflammatory diseases or the MYD88 L265P mutation. He met the diagnostic criteria for SchS and was treated with bortezomib, leading to a significant improvement in clinical symptoms and a decline in IgMκ monoclonal protein levels. The patient tolerated the treatment well. This case suggests that bortezomib may be considered as a potential treatment option for SchS, in addition to anti-IL-1 therapies and bruton tyrosine kinase (BTK) inhibitors.